Human Resource Psychology Perspective on Profession Change as a Solution for Cashless Policy at PT Jasa Marga Purbaleunyi - Angga Dewi Anggreni, Ratih Hurriyati , Lili Adi Wibowo (International Journal of Advanced Science and Technology, 2020)
e-Toll is an electronic card allowing faster and more efficient toll entry payment in Indonesia. In addition to being the first step in modernizing money collection, it is also intended to reduce rule violations since toll officers do not receive direct payments. However, the policy of using e-Toll on the toll road certainly affects the many toll booth employees. The situation as described above occurs at PT. Jasa Marga Purbaleunyi branch, which is engaged in services, especially toll road maintenance services. In this case, this research seeks to further investigate the Professional Transfer Program and its influence on employee psychology at PT. Jasa Marga Purbaleunyi Branch. PT. Jasa Marga has established a cashless policy or the implementation of a non-cash payment system, which is a direct program from the government. With the existence of this policy, Jasa Marga issued a professional transfer policy for employees at the Toll Gate. Based on research results, 82% of the toll booth employees who participated in this program felt that profession change was the right solution for them. It was concluded that the policy was suitable in dealing with the cashless policy.